Transcription, edition, translation and critical analysis of biographical poems contributed by S E K Mqhayi to early IsiXhosa newspapers - Mazwi, Ntombomzi R (Rhodes University, Faculty of Humanities, School of Languages, 2017)
During the nineteenth century secular creative literature produced by missionaries and publishers was designed for the educational market and for school children and there was nothing for adults. Works of isiXhosa literature was controlled in content and freely edited by the missionaries to satisfy the demands of educational syllabuses. As a result, students at universities, scholars of literature and academics in higher education are lacking primary documents on this literature and therefore are forced to study the limited and unavailable literature books. This thesis concentrates on the work of a particular isiXhosa writer, namely that of S.E.K. Mqhayi. The earlier writers like S.E.K. Mqhayi, J.J.R. Jolobe, G.B. Sinxo and others made their mark in South African literature and culture. Their works were published in journals and newspapers in isiXhosa by the missionaries. This means isiXhosa literature can be found in abundance in the earlier newspapers. What needs to be addressed is how the South African community and literature scholars mentioned above could have access to that work. Mqhayi is well known as the father of the isiXhosa language because of his substantial literary and linguistic contribution to the development of the language. As already mentioned he made his contribution through written work which was published in various newspapers of his time and unfortunately most people are unable to access this material, hence the focus of this thesis. The vast majority of his journalism remains as yet uncollected. However, scholars like Opland (1983) and Saule (1989) made some effort to bring this information to the public through their extensive research. S.E.K. Mqhayi's popular poems have been published and analyzed over the last century and more recently (Qangule 1979; Kuse 1979; Opland 1983; Saule 1989 & 1996; Ntuli & Swanepoel 1993 and Opland 2009). However, in terms of quantity and value, these are negligible compared to what Mqhayi has published. There are still numerous of Mqhayi's poems that would add value to the study and history of isiXhosa literature. The main aim of this research is to carry on from where these scholars left off and to bring to the fore the legacy Mqhayi left to the South African people. Hence, thirty (30) poems on people by S.E.K. Mqhayi have been transcribed from the old newspapers, re- typed, translated into English and analysed. These poems are largely published in newspapers but have never been subsequently republished, and hence they are almost completely unknown. The thirty (30) poems have been selected with the assistance of Professor Jeff Opland, a retired Professor from the University of London's School of Oriental and African Studies (SOAS). The poems are from his Opland Collection of Xhosa Literature housed in Godalming, United Kingdom. They are presented in the manner in which they appeared originally, that is, in terms of isiXhosa orthography during the times of Mqhayi's writing (Diplomatic Presentation). The data is analysed and discussed in relation to how Mqhayi's biographical poems can give insight not only to Mqhayi's subjects of praise, but into how he uses historical, political and sociocultural contexts in the praises of his subjects, meaning that the discussion revolves around the practice of the Historical-Biographical Criticism. The poems are translated into English to allow for this literature not only to be disseminated among isiXhosa speakers, but also to speakers of other languages who understand English. The translation method chosen is the one believed to produce the originality of the source text and sameness of meaning in the target text which is regarded as equivalence. This thesis therefore is an investigation into 30 poems selected from biographical poems written by S.E.K. Mqhayi in newspapers during the period 1899-1944. In essence this thesis presents an in-depth analysis of Mqhayi's poems against the backdrop of oral literary theory as expounded by theorists who have grappled with the orality-literacy debate, a debate which directly informs Mqhayi's poetry as he was the first oral poet to transition between orality and literacy.,Uncwadi oluveliswe kwishumi elinesithoba lamakhulu eminyaka ziimishinari nabapapashi lwalwenzelwe izifundiswa kunye nabantwana besikolo kwaye akukho msebenzi mninzi ofumanekayo owawenzelwe abantu basekuhlaleni. Umsebenzi omninzi wokubhaliweyo kuncwadi lwesiXhosa wawulawulwa, uhlelwa kwaye ulungiselelwa uqingqo lwezifundo. Oko ke kuye kwabangela ukuba abafundi abakumaziko emfundo ephakamileyo, iimfundi zoncwadi kunye nabahlohli zingabinawo amaxwebhu okwenene oncwadi lwesiXhosa, kwaye loo nto yenza ukuba kufundwe kwaye kwenziwe uphando ngeencwadi ezimbalwa. Olu phando ke ngoko luza kuqwalasela lugxininise kumsebenzi wombhali wesiXhosa onguS.E.K. Mqhayi. Ababhali bangaphambili abafana noo-S.E.K. Mqhayi, J.J.R. Jolobe, G.B. Sinxo nabanye bashiya ifuthe elikhulu kuncwadi nenkcubeko yoMzantsi Afrika. Imisebenzi yabo yayipapashwe ziimishinari ngesiXhosa kuluhlu lwemibhalo namaphephandaba. Oko ke kuthetha ukuthi le misebenzi yesiXhosa iyafumaneka kumaphepha-ndaba angaphambili. Okufuneka kulungisiwe yindlela abemi boMzantsi Afrika kunye nezi mfundi zoncwadi zikhankanywe ngentla zingathi ziwufumane lo msebenzi waba babhali bangaphambili. UMqhayi waziwa ngokuba yinkcuba- buchopho yolwimi lwesiXhosa kwaye udlale indima enkulu kakhulu ekuphuhliseni ulwimi lwesiXhosa. Njengokuba sele ikhankanyiwe ngentla, umsebenzi wakhe upapashwe kumaphephandaba awohlukeneyo wela xesha wayesaphila kwaye kungelishwa ke ukuba abantu abaninzi abakwazi ukuwufumana loo msebenzi. Eminye yemisebenzi yakhe emininzi ke kodwa ayiqokelelwanga. Iingcali ezifana noo-Opland (1983) noSaule (1989) zaye zenza uphando olukhulu zizama ukuzisa olu lwazi eluntwini, kodwa oko akwanelanga. Kwiminyaka edlulileyo imibongo edumileyo ka-S.E.K. Mqhayi sele yapapashwa (Qangule, 1979; Kuse, 1979; Opland, 1983 & 2009; Saule, 1989 & 1996; Ntuli & Swanepoel, 1993). Nangona kunjalo ke isekhona eminye imibongo kaMqhayi engekaveli nenokuthi ibe nenxaxheba kakhulu ekufundeni nasekufundiseni uncwadi lwesiXhosa. Olu phando ke kukuqhubeka apho aba babhali bakhankanyiweyo bayeke khona ukuzisa phambili umsebenzi nelifa elashiywa nguMqhayi kubemi baseMzantsi Afrika. Kungoko ke imibongo engabantu engama-30 kaMqhayi iza kuthi ikhutshelwe isuka kumaphephandaba akudala, iguqulelwe esiNgesini ze ihlahlelwe. Uninzi lwale mibongo ipapashwe kumaphephandaba akudala kwaye zange iphinde ipapashwe kwenye indawo, kungoko ke ingaziwa kakhulu. Ukukhethwa kwale mibongo ingama-30 kuncediswe nguNjingalwazi uJeff Opland, uNjingalwazi odla umhlala-phantsi weYunivesithi yase-London kwiSikolo seZifundo ngezaseAfrika naseMpumalanga (SOAS). Le mibongo isuka kuluhlu lwakhe athe waluqokelela nolubizwa ngokuba yi-Opland Collection of Xhosa Literature oluse- Godalming, e-United Kingdom. Indlela le mibongo eza kuthi ibhalwe ngayo yileyo uMqhayi wayeyibhale ngayo ngexesha lakhe. Le mibongo ihleliwe kwaye oko kubhaliweyo malunga nayo kuquka indlela apho imibongo kaMqhayi ngobomi babantu kuthi kubonise indlela abonga nabonisa ngayo izinto zoPolitiko, zakudala nezasekuhlaleni ezazisenzeka ngela xesha. Indlela ethi konke oku kuthi kuvele kule mibongo kaMqhayi kwaye kuya kuthi kuvezwe kolu phando. Ukuguqulelwa kwale mibongo esiNgesini kuya kuthi kuncede ukuba nabo bangasithethiyo isiXhosa bakwazi ukufumana le mibongo. Indlela esetyenzisiweyo yoguqulo-lwimi yale mibongo yileyo ivumela ukuba umbhalo uguqulelwe ngokufanayo nombhalo-ntsusa kwaye intsingiselo kumbhalo ekuguqulelwa kuwo ingatshintshi. Lo misebenzi ke ngoko uluphando lwemibongo engabantu ekhethiweyo engama30 ebhalwe nguSEK Mqhayi kumaphephandaba kwimiminyaka u1899 - 1944. Umongo wolu phando kukwenza uhlalutyo - nzulu lwemibongo kaMqhayi eyaleka kuphando - lwazi osele lwenziwe njengoko lucaciswa ziingcali ezithe zazamana nengxoxo yoncwadi lomlomo, ngxoxo leyo ethe yachaphazela ngokumandla umongo wezibongo zikaMqhayi njengembongi yokuqala ukuwela ukusuka kuncwadi lomlomo ukuya kuncwadi olubhaliweyo.
Keywords: Mqhayi, S E K -- Criticism and interpretation; Mqhayi, S E K -- Translations; Xhosa language -- Transcription; Xhosa poetry -- History and criticism; Xhosa poetry -- Translations